Maternal components of RNA‐directed DNA methylation are required for seed development in Brassica rapa. (23rd April 2018) - Grover, Jeffrey W.; Kendall, Timmy; Baten, Abdul; Burgess, Diane; Freeling, Michael; King, Graham J.; Mosher, Rebecca A.
Summary: Small RNAs trigger repressive DNA methylation at thousands of transposable elements in a process called RNA‐directed DNA methylation (RdDM). The molecular mechanism of RdDM is well characterized in Arabidopsis, yet the biological function remains unclear, as loss of RdDM in Arabidopsis causes no overt defects, even after generations of inbreeding. It is known that 24 nucleotide Pol IV‐dependent siRNAs, the hallmark of RdDM, are abundant in flowers and developing seeds, indicating that RdDM might be important during reproduction. Here we show that, unlike Arabidopsis, mutations in the Pol IV‐dependent small RNA pathway cause severe and specific reproductive defects in Brassica rapa . High rates of abortion occur when seeds have RdDM mutant mothers, but not when they have mutant fathers. Although abortion occurs after fertilization, RdDM function is required in maternal somatic tissue, not in the female gametophyte or the developing zygote, suggesting that siRNAs from the maternal soma might function in filial tissues. We propose that recently outbreeding species such as B. rapa are key to understanding the role of RdDM during plant reproduction. Significance Statement: Although RNA‐directed DNA methylation has repeatedly been implicated in reproduction, there are no developmental phenotypes associated with loss of this pathway in Arabidopsis. We show that in Brassica rapa, an outbreeding species closely related to Arabidopsis, RdDM is required in maternal somatic tissues for development of seeds after fertilization.